Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jaac.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Biomarker and Early Temperament Predict Increased Internalizing Symptoms After a Natural Disaster

Abstract: Objective Although most people will experience a traumatic event, only some will develop significant psychological symptoms in the aftermath. In the current study, we utilize a preexisting longitudinal study located in Long Island to examine the impact of Hurricane Sandy on internalizing symptoms in a large sample of children. We focused on temperamental fear and a biomarker of risk for anxiety, the error-related negativity (ERN). The ERN is a negative deflection in the event-related potential (ERP) occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…Previous studies have found that among children high in behavioral inhibition, an increased ERN predicts anxiety symptoms later in development (Lahat et al, 2014;McDermott et al, 2009). Furthermore, we have extended this work and found that children with an elevated ERN are particularly prone to environmentally induced increases in anxiety symptomsin a large sample of children who experienced Hurricane Sandy, it was the children who were high in temperamental fear and had an increased ERN who displayed posthurricane symptom increases (i.e., Hurricane Sandy; Meyer, Danielson et al, 2017). Important to the validation of the ERN as a biomarker of clinical anxiety, we have also found that an increased ERN in 6 year old children predicts the onset of new anxiety disorders 3 years later, even when controlling for baseline anxiety symptoms (Meyer, Hajcak, Torpey-Newman, Kujawa, & Klein, 2015).…”
Section: Introductionmentioning
confidence: 62%
“…Previous studies have found that among children high in behavioral inhibition, an increased ERN predicts anxiety symptoms later in development (Lahat et al, 2014;McDermott et al, 2009). Furthermore, we have extended this work and found that children with an elevated ERN are particularly prone to environmentally induced increases in anxiety symptomsin a large sample of children who experienced Hurricane Sandy, it was the children who were high in temperamental fear and had an increased ERN who displayed posthurricane symptom increases (i.e., Hurricane Sandy; Meyer, Danielson et al, 2017). Important to the validation of the ERN as a biomarker of clinical anxiety, we have also found that an increased ERN in 6 year old children predicts the onset of new anxiety disorders 3 years later, even when controlling for baseline anxiety symptoms (Meyer, Hajcak, Torpey-Newman, Kujawa, & Klein, 2015).…”
Section: Introductionmentioning
confidence: 62%
“…This suggests that individuals at familial risk for anxiety disorders also show increased ERN amplitudes. Additional support for increased ERN as a candidate endophenotype for anxiety comes from studies suggesting that ERN magnitude could be used to predict the onset of GAD (Meyer et al, ), social anxiety (Lahat et al, ), and anxiety symptoms collapsed across different DSM categories (McDermott et al, ; Meyer et al, ; Meyer, Hajcak et al, ). Collectively, these results support the idea that increased ERN amplitudes represent a shared endophenotype for OCD and anxiety (Olvet & Hajcak, ; Riesel et al, , in press).…”
Section: Section 2: Enhanced Neural Error Signals As Endophenotype Fomentioning
confidence: 99%
“…Importantly, the clinical relevance of error‐related brain activity is supported by studies demonstrating its predictive validity for the onset of symptoms across various mental disorders (Anokhin & Golosheykin, ; Lahat et al, ; Meyer, Hajcak et al, ; Meyer et al, ). In longitudinal studies, ERN predicted the onset of anxiety symptoms in children and adolescents (Lahat et al, ; Lamm et al, ; Meyer, Hajcak et al, ; Meyer et al, ) and the development of symptoms in response to critical life events such as a natural disaster (Meyer et al, ). Further, in preschool‐aged individuals, observed hyperactive performance monitoring at the behavioral level predicted the onset of OCD and reduced ACC volume over 12 years (Gilbert, Barclay, Tillman, Barch, & Luby, ).…”
Section: Section 3: Clinical Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our findings extend the few studies showing that, consistent with diathesis-stress models, life stressors moderate associations of early temperamental and neural vulnerabilities with subsequent internalizing psychopathology (41, 42). Finally, our data suggest the importance of considering risk factors at many levels simultaneously because temperamental and neural diatheses can combine to create potent vulnerabilities to internalizing symptoms in the face of major stressors (38, 43). …”
Section: Discussionmentioning
confidence: 89%